Privatization and labor force restructuring around the world - Alberto Chong; Florencio López-De-Silanes (Fondazione Eni Enrico Mattei (FEEM), 2002)
Critics of privatization argue that poor labor force restructuring is a key concern and that governments should establish better retrenchment programs. Using new data from arandom sample of 400 companies in the world, we test competing theories about the wisdom of retrenchment programs and their effect on prices paid by buyers and rehiringpolicies by private owners after privatization. Our results show that adverse selection plagues retrenchment programs carried out by governments before privatization. Controlling for endogeneity, several labor retrenchment policies yield a negative impacton net privatization prices. In confirmation of the adverse selection argument, various types of voluntary downsizing lead to a higher probability of rehiring the same workers by the new private owners. Compulsory skill-based programs are the only type of program that is marginally associated with higher prices and lower rehiring rates after privatization, but the political and economic costs of this policy may make it somewhat unpractical. A qualified `do not intervene' appears to be the safest bet in labor retrenchment before privatization.
Keywords: G32; H10; J45; O1; 330; Privatization; downsizing; adverse selection; corporate governance; Privatisierung; Erwerbspersonenpotenzial; Welt